2014
DOI: 10.1159/000363444
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous or Respiratory Exposures to Peanut Allergens in Mice and Their Impacts on Subsequent Oral Exposure

Abstract: Background: Recent data suggested that non-gastrointestinal exposure can lead to sensitisation to food allergens. We thus assessed the immune impact of respiratory or cutaneous exposure to peanut proteins on non-altered epithelium and investigated the effect of such pre-exposure on subsequent oral administration of peanut. Methods: BALB/cJmice were exposed to purified Ara h 1 or to a non-defatted roasted peanut extract (PE) by simple deposit of allergens solutions on non-altered skin or in the nostrils. Exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…The link between eczema and food allergy is attributed to low-dose cutaneous exposure to an allergen that may promote allergic sensitization, whereas early oral consumption induces tolerance [1] . This is supported by animal models [24] and by reports suggesting that exposure in infancy to skin preparations, tabletops or hands containing food allergen increases the risk of food allergy in those with eczema (OR 2.4, 95% CI 1.9-3.0 [1,25,26] to OR 6.8, 95% CI 1.4-32.9) [27][28][29] .…”
Section: Discussionmentioning
confidence: 70%
“…The link between eczema and food allergy is attributed to low-dose cutaneous exposure to an allergen that may promote allergic sensitization, whereas early oral consumption induces tolerance [1] . This is supported by animal models [24] and by reports suggesting that exposure in infancy to skin preparations, tabletops or hands containing food allergen increases the risk of food allergy in those with eczema (OR 2.4, 95% CI 1.9-3.0 [1,25,26] to OR 6.8, 95% CI 1.4-32.9) [27][28][29] .…”
Section: Discussionmentioning
confidence: 70%
“…Patches have been left for 24 h [26, 36] or a longer period of exposure such as 3 days [37, 38]. In this study, the gluten products were left on the skin for 1 h, a short period of allergen exposure similar to the 40 min used in the study by Wavrin et al [39]. These short periods of allergen exposure may correspond more closely to what consumers experience and may not alter the permeability of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that inhalational exposure to peanut and other food allergens can result in sensitization . However, these studies involved airway delivery of either allergen alone or in combination with cholera toxin as an adjuvant.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of PA subjects react upon their first known ingestion of peanut, suggesting sensitization occurs through non‐oral routes of exposure. While there is evidence that cutaneous exposure to peanut through an impaired skin barrier can result in sensitization, recent studies in rodents have shown that inhalational exposure to peanut can also lead to sensitization and anaphylaxis to peanut allergen . In addition, peanut‐specific CD4 + T cells from PA subjects express both airway‐ and skin‐homing chemokine receptors, suggesting that peanut sensitization may occur through the skin and respiratory tract .…”
Section: Introductionmentioning
confidence: 99%